Red LED Light Acts on the Mitochondrial Electron Chain of Donkey Sperm and Its Effects Depend on the Time of Exposure to Light - Catalán, Jaime; Papas, Marion; Trujillo-Rojas, Lina; Blanco-Prieto, Olga; Bonilla-Correal, Sebastián; Rodríguez-Gil, Joan E.; Miró, Jordi; Yeste, Marc (Frontiers in Cell and Developmental Biology, 2020)
This work aimed to investigate how stimulation of donkey sperm with red LED light affects mitochondrial function. For this purpose, freshly diluted donkey semen was stimulated with red light for 1, 5, and 10 min, in the presence or absence of oligomycin A (Omy A), a specific inhibitor of mitochondrial ATP synthase, or FCCP, a specific disruptor of mitochondrial electron chain. The results obtained in the present study indicated that the effects of red LED light on fresh donkey sperm function are related to changes in mitochondria function. In effect, irradiation of donkey sperm resulted in an increase in mitochondrial membrane potential (MMP), the activity of cytochrome C oxidase and the rate of oxygen consumption. In addition, in the absence of oligomycin A and FCCP, light-stimulation augmented the average path velocity (VAP) and modified the structure of motile sperm subpopulations, increasing the fastest and most linear subpopulation. In contrast, the presence of either Omy A or FCCP abolished the aforementioned effects. Interestingly, our results also showed that the effects of red light depend on the exposure time applied, as indicated by the observed differences between irradiation protocols. In conclusion, our results suggest that exposing fresh donkey sperm to red light modulates the function of their mitochondria through affecting the activity of the electron chain. However, the extent of this effect depends on the irradiation pattern and does not exclude the existence of other mechanisms, such as those related to thermotaxis.